Sophie's world : a novel about the history of philosophy - Gaarder, Jostein (Berkley Books, 1996)
Discovering two thought-provoking philosophical questions in her mailbox, Sophie enrolls in a correspondence course with a mysterious philosopher and begins to receive some equally unusual letters. Reprint.